Estimasi Perubahan Kualitas Udara Berbasis Citra Satelit Penginderaan Jauh Di Sekitar PLTU Cirebon - Moh. Dede; Millary Agung Widiawaty; Nurhanifah Nurhanifah; Arif Ismail; Ajeng Randhita Prabatiwakya Artati; Amniar Ati; Yanuar Rizky Ramadhan (Jambura Geoscience Review, 2020)
Steam power plant construction and operation is an effort to meet electricity needs. In Indonesia, two steam power plants were built and changed the landscape in Cirebon. The presence of Cirebon steam power plants has disturbed the community and potential to decrease air quality. This study aims to estimate air quality changes around the power plants based on remote sensing satellite imageries. The main data in this study obtained from Landsat-8 OLI (2019) and Landsat-7 ETM (2004) satellite imageries were processed with four parameters of air quality algorithm namely PM10, CO, SO2, and NOx on AOI with ranging of 2000 m from the source point. Validation uses comparative data from MODIS and Sentinel-2 MSS satellite imageries in the same period. Changes analysis in air quality used the Mann-Whitney method (U-Test). This research shows that the Landsat series satellite imagery is suitable to be used as the main data for estimating air quality because it has a similar pattern to comparable data. The Cirebon PLTU operation caused a significant increase in CO levels of 1.25 mg/l on a wide range. In other air quality parameters such as PM10, SO2 and NOx were decreased.